Aerodynamic analysis of a step adjustment method for blade pitch of a VAWT. Issue 188 (May 2019) - Guo, Yonghui; Li, Xiaochang; Sun, Lanxin; Gao, Ye; Gao, Zheming; Chen, Linjun
Abstract: Vertical-axis wind turbines (VAWTs), which are considered an important wind energy conversion device, have recently received renewed attention. Researchers are investigating the pitch angle control method to improve the wind energy utilization efficiency of VAWTs. In this study, ANSYS Fluent is used to investigate the aerodynamic performance of two-dimensional VAWTs. Different pitch angles are investigated using unsteady Reynolds-averaged Navier–Stokes calculations, and turbulence is modeled with the shear stress transport k–ω model. Four quartiles are defined for the azimuthal angle of a rotation period: upwind (45 ° < θ < 135 ° ), leeward (135 ° < θ < 225 ° ), downwind (225 ° < θ < 315 ° ), and windward (315 ° < θ < 45 ° ). Furthermore, the sliding-mesh technique and a user-defined function are applied to adjust the pitch angle of the wind turbine blades in different azimuthal zones. This study proposes a pitch angle control method that effectively improves the efficiency of VAWTs by comprehensively analyzing the aerodynamic performance of the wind turbine and power coefficient ( C p ) variation in each zone. The results indicate that an appropriate pitch angle control solution can significantly improve the efficiency of the wind turbine. Compared to a fixed pitch angle of 0°, an approximately 17.0% increase in C p can be achieved and, compared to the optimal fixed pitch angle −1°, an approximately 12.0% increase in C p can be achieved. Highlights: Pitch angles of −5° to +4° and the effect on the VAWT power are investigated. Obtain the optimal pitch angle for each quartile to optimize blade pitch control. Suitable pitch angle control solution increases the turbine C p by 12.0% compared to ADNI.